2003
DOI: 10.1111/j.1745-459x.2003.tb00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Taste Panel Efficiency During Evaluation of the Sensory Quality of Roncal Cheese

Abstract: A statistical study was performed on the scores awarded by a taste panel over a full Roncal cheese manufacturing season. The panel evaluations were part of a quality control program carried out on that cheese under the auspices of the Appellation of Origin for Roncal cheese by panelists previously trained and qualified as proficient. Analysis of variance and factor analysis were performed to examine variability for the different attributes and the influence of such factors as cheesemaking plant and the manufac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In the present research, the samples were served by a simultaneous multiple way (attribute by attribute), which allows for better comparative discrimination among the products, getting high levels of discrimination and repeatability in the panel [31]. The results of judge factor determined some discrepancies in the use of the intensity' scale, which is explained by inter-individuals differences [12]. In the case of the session factor, the results showed that data from both panels were repetitive in the majority of attributes; this disagrees with the results presented by [4], who evaluated 16 sensory characteristics of products made from walnut with panels located in Italy, Spain and France, and they found a significant effect (P < 0.05) on 6, 4 and 3 attributes, respecttively.…”
Section: Evaluation Of the Performance Of Each Trainedmentioning
confidence: 86%
See 4 more Smart Citations
“…In the present research, the samples were served by a simultaneous multiple way (attribute by attribute), which allows for better comparative discrimination among the products, getting high levels of discrimination and repeatability in the panel [31]. The results of judge factor determined some discrepancies in the use of the intensity' scale, which is explained by inter-individuals differences [12]. In the case of the session factor, the results showed that data from both panels were repetitive in the majority of attributes; this disagrees with the results presented by [4], who evaluated 16 sensory characteristics of products made from walnut with panels located in Italy, Spain and France, and they found a significant effect (P < 0.05) on 6, 4 and 3 attributes, respecttively.…”
Section: Evaluation Of the Performance Of Each Trainedmentioning
confidence: 86%
“…The three-way ANOVA results with interaction (Product × Judge) for the performance evaluation of the UMAR panel are shown in Table 2; this group was highly discriminating (P < 0.01) in the most of the attributes except for the aroma to serum. The judge factor revealed differences in the use of the scale on white color, soft to the touch, salty, lumpy in the mouth and soft in the mouth attributes; this effect might been due to inter-individual variation because of differences in the use of the intensity' scale by the subjects [12] and by the difference in training time of the panelists [4,28]. The session factor revealed that the panel was repetitive on all attributes except on the salty attribute; while the interaction factor determined that there were differences in the classification of cheeses for smell of rennet and aroma to serum attributes.…”
Section: Evaluation Of the Performance Of Each Trainedmentioning
confidence: 92%
See 3 more Smart Citations